Appropriate Innovation for Asian Emerging Markets in a Digital World: A Strategic Framework - George Abonyi; David Abonyi (Theory, Methodology, Practice, 2022)
Growth in spending in Asian emerging economies will be driven to a large extent by lower-middle income and lower-income households. They constitute a vast “2nd tier” underserved market, much of it located in smaller cities, towns, and rural areas. This study develops a framework for appropriate innovation strategy aimed at this substantial market. We identify key relevant characteristics of the leading Asian emerging economies of ASEAN, China and India; that often do not get sufficient attention. The proposed strategic framework then builds on selected examples of appropriate innovation; incorporates the potentially important role of unconventional partnership between business and social enterprise for this market; and develops the supporting role of digital technology, in particular, additive manufacturing (3D printing). We conclude by presenting policy implications of an appropriate innovation strategy, involving government-business collaboration.